“My colours flash in the sunshine of the racecourse”. Owning a thoroughbred in South Africa - (:unkn) unknown (My University, 2022)
The author examines how a racehorse can be viewed as a “luxury good”. She shows that the thoroughbred is the result of a process of enhancement, “enrichment”, which transforms it into a “luxury good”. This enhancement of the animal is achieved through the creation of a genealogy that immortalizes it, as well as through the numerous accounts of its sensational victories. The horse as such does not belong to a special class of goods – even if one bears in mind that it is a living being, it rather enters into a special register of consumption, which is part of a social world, built specifically around the animal. The analysis of this social world also allows the author to explore the sociopolitical transformations that post-apartheid South African society is undergoing.
Keywords: African Research